Study on awareness regarding snake bite hazards among people working in agriculture sector and health education about preventive and first aid measures - Guthi, Visweswara Rao; Arepalli, Sreedevi; Toka, Sivakala; Kakamanu, Lohitha Bala; Kakamanu, Lakshmi Sindhura (International Journal Of Community Medicine And Public Health, 2019)
Background: Snake bite is a common medical emergency and an occupational hazard, more so in tropical India, where farming is a major source of employment. In India alone, it has been estimated that as many as 2.8 million people are bitten by snakes, and 46 900 people die from snakebite every year. The objective of the present study is to study the awareness about hazards of snake bite and to educate about preventive and first aid measures for snake bite. Methods: This study was a community based longitudinal study conducted in 7 villages near Kurnool town. The sample size was 230. From each agriculture workers after obtaining consent pre-test was done to know their awareness regarding hazards of snake bites in agriculture fields and preventive and first aid measures in each village followed by post-test after health education. Results: In this study 230 agriculture workers were participated. Among them 108 (46.95%) were males and 122 (53.1%) were females. Most of the study population were in the age group of 31-40 years (36.9%). Using torch during nights was 68.7% it was increased significantly to 83% after health education, using foot wear was only in 30.4% and increased significantly to 100%, using stick was in 76% and increased to 100% significantly. Conclusions: The practice of using torch, wearing footwear, using stick while on field, avoid sleeping on ground in the field were significantly improved after health education. The first aid measure measures after snake bite like immobilization of bitten limb, reassure the person bitten by snake, avoid suctioning, avoiding tourniquet were also improved significantly after health education.